An evaluation of adverse drug reactions monitoring at a pharmacovigilance unit under pharmacovigilance program of India in a tertiary care hospital of Haryana - Kharb, Preeti; Mittal, Niti; Gupta, Mahesh C. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions (ADRs) are among top 10 causes of mortality in patients. Pharmacovigilance programme of India (PvPI) is a step towards participation in the WHO programme for International Drug Safety Monitoring. The present article is an evaluation of the incidence and the patterns of ADRs from the reports collected from various clinical departments of this hospital. Methods: A total of 859 suspected ADR reports submitted to the pharmacovigilance unit at Department of Pharmacology under PvPI were evaluated for 6 months with respect to demographics, causative drug, organ system involvement, severity and seriousness of ADRs. The causality assessment was carried out by using WHO assessment method and Naranjo’s scale. Results: Males experienced more (66.33%) ADRs. The highest percentage (45.83%) of ADRs was seen in the age group of 46-60 years (35.33%), followed by 16-30 years (25.5%). The most common drug group causing ADRs was antimicrobials (43.37%), followed by anticancer and immunosuppressive agents (29.02%). The gastrointestinal system (31.43%) was most prone system, followed by generalized body reactions (22.93%) and cutaneous reactions (17.11%). 662 (77%) ADRs were non-serious, 197 (22.9%) were serious. On severity scale, 682 (79.39%) were mild, 168 (19.65%) moderate and only 9 (1.05%) ADRs were severe out of which three were fatal. As per WHO assessment method 66.94% ADRs were probable and 33.06% possible. The probability was comparable with Naranjo’s scale. Conclusion: ADRs to drugs happen commonly, and their reporting is important for the early recognition and prevention of ADRs and will also help in generating signals. ADR monitoring not only acts as an alerting mechanism for physicians, but helps the regulatory authorities in making the policy decision.